Factors associated with students' oral test performance / Norhamimah Rani - Rani, Norhamimah (2008)
Students’ test anxiety was identified to be one of the influencing factors which might give impact to their overall language performance (Chan and Wu, 2004). Accordingly, the main purpose of the study was to examine the relationships between the performance of students in School-based Oral English Test and their anxiety level, attitudes and perceptions towards language learning and their learning environment. The main problems students faced based on their own opinion were also investigated. A descriptive-correlational research design was employed in this study. The quantitative and qualitative data collection involved the use of a questionnaire, open-ended questions and interviews. Participants were 108 form four students and two English teachers in a boarding school in Terengganu. Results from the quantitative data indicated that there was a weak correlation between the Oral English scores and the students’ anxiety level, attitudes and learning environment. However, qualitative data revealed the considerable magnitude of influence the independent variables had on the oral performance. Qualitative data also demonstrated other contributing factors like grammar skills and vocabulary which emerged from interviews and open-ended questions. This indicated that there were many variables influencing the students’ speaking abilities. The findings of this study generally can help the teachers and administrators of the school studied and other boarding schools in Terengganu to plan and identify the best ways and strategies to further improve the students’ perceptions and practices of communicating in English.